Microcirculation of the gastric mucosa and the efficiency of standard eradication therapy in patients with duodenal peptic ulcer - Jafar Akermi (Zaporožskij Medicinskij Žurnal)
Purpose: explore the features of the condition of the gastric mucosa in patients with duodenal ulcer in the background of the standard triple therapy.